Low-Circulating Homoarginine is Associated with Dilatation and Decreased Function of the Left Ventricle in the General Population - Martin Bahls; Dorothee Atzler; Marcello R.P. Markus; Nele Friedrich; Rainer H. Böger; Henry Völzke; Stephan B. Felix; Edzard Schwedhelm; Marcus Dörr (Biomolecules, 2018)
Low homoarginine is an independent marker of mortality in heart failure patients and incident cardiovascular events. Whether homoarginine is related with healthier cardiac structure and function is currently unclear. We used data of the population-based “Study of Health in Pomerania” (SHIP-Trend) to assess this relation. Homoarginine was measured in serum using liquid chromatography-tandem mass spectrometry. Linear regression models assessed the relation between homoarginine and several structural as well as functional parameters and N-terminal pro B-type natriuretic peptide (NTproBNP). All models were adjusted for age, sex, body mass index, and renal function. A total of 3113 subjects (median age 48 (25th percentile 37 to 75th percentile 60) years, 46% male) were included. A standard deviation decrease in homoarginine was associated with a larger left ventricular diastolic diameter (0.3; 95%-confidence interval (CI): 0.2 to 0.5 mm; p < 0.001), left ventricular systolic diameter (0.38; 95%-CI: −0.22 to 0.54 mm; p < 0.001) as well as a less relative wall thickness (–0.003 95%-CI: −0.006 to −0.0008; p = 0.01), left ventricular ejection fraction (–0.47; 95%-CI: –0.79 to −0.15%; p < 0.01) and fractional shortening (−0.35; 95%-CI: −0.62 to 0.07%; p = 0.01). Low homoarginine was also related to higher NTproBNP (−0.02 95%-CI: −0.034 to −0.009 log pg/mL; p < 0.01). Lower serum homoarginine is associated with dilatation of the heart and decreased function. Prospective clinical studies should assess if homoarginine supplementation improves cardiac health in subjects with low serum concentrations.